Fortunes of Feminism: From State-Managed Capitalism to Neoliberal Crisis - Fraser, Nancy (Verso Books, 2013)
Charts the history of women’s liberation and calls for a revitalized feminism.Nancy Fraser’s major new book traces the feminist movement’s evolution since the 1970s and anticipates a new—radical and egalitarian—phase of feminist thought and action.During the ferment of the New Left, “Second Wave” feminism emerged as a struggle for women’s liberation and took its place alongside other radical movements that were questioning core features of capitalist society. But feminism’s subsequent immersion in identity politics coincided with a decline in its utopian energies and the rise of neoliberalism. Now, foreseeing a revival in the movement, Fraser argues for a reinvigorated feminist radicalism able to address the global economic crisis. Feminism can be a force working in concert with other egalitarian movements in the struggle to bring the economy under democratic control, while building on the visionary potential of the earlier waves of women’s liberation. This powerful new account is set to become a landmark of feminist thought.
Keywords: critical theory; feminism; feminist theory; triple movement

A Triple Movement? - Fraser, Nancy (New Left Review, 2013)
Keywords: double movement; social protection; triple movement